Class I Myosins Have Overlapping and Specialized Functions in Left-Right Asymmetric Development in Drosophila. Issue 4 (6th February 2015) - Okumura, Takashi; Sasamura, Takeshi; Inatomi, Momoko; Hozumi, Shunya; Nakamura, Mitsutoshi; Hatori, Ryo; Taniguchi, Kiichiro; Nakazawa, Naotaka; Suzuki, Emiko; Maeda, Reo; Yamakawa, Tomoko; Matsuno, Kenji
Abstract: The class I myosin genes are conserved in diverse organisms, and their gene products are involved in actin dynamics, endocytosis, and signal transduction. Drosophila melanogaster has three class I myosin genes, Myosin 31DF ( Myo31DF ), Myosin 61F ( Myo61F ), and Myosin 95E ( Myo95E ). Myo31DF, Myo61F, and Myo95E belong to the Myosin ID, Myosin IC, and Myosin IB families, respectively. Previous loss-of-function analyses of Myo31DF and Myo61F revealed important roles in left–right (LR) asymmetric development and enterocyte maintenance, respectively. However, it was difficult to elucidate their roles in vivo, because of potential redundant activities. Here we generated class I myosin double and triple mutants to address this issue. We found that the triple mutant was viable and fertile, indicating that all three class I myosins were dispensable for survival. A loss-of-function analysis revealed further that Myo31DF and Myo61F, but not Myo95E, had redundant functions in promoting the dextral LR asymmetric development of the male genitalia. Myo61F overexpression is known to antagonize the dextral activity of Myo31DF in various Drosophila organs. Thus, the LR-reversing activity of overexpressed Myo61F may not reflect its physiological function. The endogenous activity of Myo61F in promoting dextral LR asymmetric development was observed in the male genitalia, but not the embryonic gut, another LR asymmetric organ. Thus, Myo61F and Myo31DF, but not Myo95E, play tissue-specific, redundant roles in LR asymmetric development. Our studies also revealed differential colocalization of the class I myosins with filamentous (F)-actin in the brush border of intestinal enterocytes.